2008
DOI: 10.1111/j.1471-0307.2008.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of sialic acid levels in the colostrum and milk of ruminants: possible role in the passive immunity against neonatal infections

Abstract: A study was conducted to determine the levels of free sialic acid in the colostrum and milk of apparently healthy indigenous Nigerian ruminants (Zebu cows, Yankassa sheep and Sokoto Red/Kano Brown goats). Haematological investigation indicates that the apparently healthy ruminants were also clinically healthy. The mean free sialic acid concentration in the colostrum of all the animal species examined was higher than those of milk and the difference in each case was statistically significant (P < 0.05). The sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Total SA reduced by 6.8 fold in Sahiwal, 6.5 fold in Tharparkar and 7.8 fold in Karan Fries. This decline was consistent with the data reported by Useh et al (2008), for the SA levels in colostrum and milk of bovines, goats and sheep. SA content in human colostrum was also observed to be five times higher than that in the mature milk (Wang et al 2001).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Total SA reduced by 6.8 fold in Sahiwal, 6.5 fold in Tharparkar and 7.8 fold in Karan Fries. This decline was consistent with the data reported by Useh et al (2008), for the SA levels in colostrum and milk of bovines, goats and sheep. SA content in human colostrum was also observed to be five times higher than that in the mature milk (Wang et al 2001).…”
Section: Resultssupporting
confidence: 93%
“…Lactation period is an important factor affecting milk composition. Concentration of SA also varies during lactation (Useh et al 2008). Thus, mid-lactation stage was selected for mature milk, as it corresponded to the stable phase of lactation curve.…”
Section: Resultsmentioning
confidence: 99%
“…The overall decrease in TS content of porcine milk, particularly protein, may in part explain the decline in Sia concentration in both gilt and sow milk during lactation. Further, Useh et al (2008) have suggested that the higher level of total Sia in colostrum compared with mature milk may relate to more com-plex interactions between Sia-GC associated with the development of mucosal immunity to combat enteric pathogens.…”
Section: Figure 2 (A)mentioning
confidence: 99%
“…Sialic acidpart of OSinclude N-acylneuraminic acids and their derivatives, with Nacetylneuraminic acid (Neu5Ac) and N-glycolylneuraminic acid (Neu5Gc) being the most abundant. In ruminants, great variations of OS concentrations are observed 59,60 . In ovines, in agreement with our results, Neu5Gc is a dominant component among the colostrum sialic acids 61 , whereas in bovine colostrum, Neu5Ac compounds are predominant with great amounts of3′-sialyllactose (3′SL) 62 .…”
Section: Colostrum Composition Dynamics Across the First 72h Post-partummentioning
confidence: 99%